Examining The Social Impact of Microfinance on Poverty Reduction - DR. SAIF UL MUJAHID SHAH; DR. ANWAR UL MUJAHID SHAH; SYED ARSHAD ALI SHAH (Journal of Business & Tourism, 2021)
As Poverty has become a global challenge for all the nations around the world, from the past many years, different strategies have been used to reduce it. However, since 1980s Microfinance has become a powerful tool to alleviate poverty and it's not adopted even in the developing countries but also developed nations have been practicing it. Many of the past studies used the economic indicators to measure the impact of microfinance on poverty reduction, and few have concentrated on the social indicators. The purpose of this research is to examine the effect of microfinance as a poverty reduction in terms of social indicators in the rural areas of northern Khyber Pakhtunkhwa, Pakistan. The objective of this research is to check whether the established NGOs in the concern areas have been successful in bringing social change in the life of the beneficiaries. For the purpose of analysis, the structural equation model is applied to a sample of 440 collected through a structured questionnaire. Results show that microfinance had a negative impact on the health and education of the beneficiaries. This research indicates that more funds and priority should be given to the education and health sector because they have equal importance as compared to the other economic indicators.